Kontribusi Motivasi Terhadap Prestasi Atlet Sepatu Roda Nomor 500 Meter: - Artamalia Rizky Fareza; Pudjijuniarto Pudjijuniarto (Indonesian Journal of Kinanthropology (IJOK), 2023)
Background: Motivation as a manifestation of psychology in the form of encouragement that occurs in each individual. According to data obtained in 2021-2022, the achievements of Surabaya roller skating athletes have decreased in achievement and in the 500 meters that follow the rules of the world champ. The purpose of this study is to determine the relationship and magnitude of motivational contribution to the achievements of roller skating athletes with the number 500 meters. Methods: This research method uses a quantitative correlation approach method. The data collection technique is to conduct a 500-meter sprint test and questionnaire. Results: The results of the data analysis obtained by calculating a correlation of 0.629 with sufficient category interpretation. While the contribution value is obtained by 40%. Conclusions: So it can be concluded, that there is a relationship between motivation and achievements of Surabaya roller skating athletes and has a motivational contribution of 40% to the achievements of Surabaya roller skating athletes with a distance of 500 meters